Indigenous-plant extracts as larvicidal agents against Culex quinquefasciatus Say - Karmegam, N.; Sakthivadivel, M.; Anuradha, V.; Daniel, T.
Bioassay studies of the laboratory-colonised larvae (LCL)and field-collected larvae (FCL)of Culex quinquefasciatus with five different concentrations of 12 different plant extracts (petroleum ether solvent)showed that the extracts of Argemone mexicana, Jatropha curcus, Pergularia extensa and Withania somnifera had acute toxicity. The benzene extracts of these four plants were tested for their toxic effects on LCL and FCL. Argemone mexicana showed acute toxicity and observations made at 31"25 ppm concentration showed larval and pupal mortality; larval-pupal intermediates; half ecdysed organisms and prolonged larval and pupal duration.
Keywords: CULEX QUINQUEFASCIATUS, PETROLEUM ETHER EXTRACT; ACUTE TOXICITY; A. MEXICANA; LABORATORY-COLONISED LARVA; FIELD COLLECTED LARVA; LARVAL-PUPAL INTERMEDIATE; HALF ECDYSIS; MORTALITY